1998
DOI: 10.1210/jc.83.9.3302
|View full text |Cite
|
Sign up to set email alerts
|

Net Increase in Stimulatory Input Resulting from a Decrease in Inhibin B and an Increase in Activin A May Contribute in Part to the Rise in Follicular Phase Follicle-Stimulating Hormone of Aging Cycling Women

Abstract: Recent studies suggest that an age-related decline in ovarian inhibin B may play a role in the increase in follicular phase FSH in menstrual cycles of older women. Considering that the peripheral feedback regulation of FSH is dictated by the overall tone of inhibins, activins, and follistatins as well as estradiol, it is essential to determine the relative inputs of all of these regulators in assessing whether the collective peripheral input to FSH is one of inhibition or stimulation. To test the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 0 publications
4
51
0
3
Order By: Relevance
“…Others, in a recent study, failed to find these correlations and concluded that although CCCT was useful as a test of ovarian reserve, there was no additional value for inhibin B testing (13). Aging women have increasing levels of FSH during early follicular phase, which in turn might be a consequence of declining secretion of inhibin by reduced number of ovarian follicles (8,25,26). Patients with high serum levels of FSH on day 3 had granulosa cells of diminished capacity for secreting dimeric inhibins (9).…”
Section: Discussionmentioning
confidence: 99%
“…Others, in a recent study, failed to find these correlations and concluded that although CCCT was useful as a test of ovarian reserve, there was no additional value for inhibin B testing (13). Aging women have increasing levels of FSH during early follicular phase, which in turn might be a consequence of declining secretion of inhibin by reduced number of ovarian follicles (8,25,26). Patients with high serum levels of FSH on day 3 had granulosa cells of diminished capacity for secreting dimeric inhibins (9).…”
Section: Discussionmentioning
confidence: 99%
“…In rats and in humans, it has become clear that both inhibin-A and inhibin-B are important for the regulation of FSH secretion (Woodruff et al 1996, Reame et al 1998, Smitz & Cortvrindt 1998; however, inhibin-B has never been isolated from ruminant follicular fluid and assays for inhibin-B do not detect this inhibin form in sheep follicular fluid (Knight et al 1998). It is at present likely that inhibin-B is not a major secretory product of the ruminant follicle.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a significant decrease in the serum levels of inhibin B during the follicular phase in women of advanced reproductive age with ovulatory cycles, concomitant with an increase in the FSH levels [76][77][78][79][80][81][82][83][84]. It has been shown that the main sources of inhibin B in the circulation are the pre-antral and small antral follicles [85][86][87].…”
Section: Menopausementioning
confidence: 99%
“…It has been shown that the main sources of inhibin B in the circulation are the pre-antral and small antral follicles [85][86][87]. The decrease in the serum inhibin B levels has been attributed to the diminishing number of these follicles in the ovaries [76][77][78][79][80][81]. It has been suggested that the resulting reduced negative feedback from inhibins on pituitary FSH secretion could be responsible for the observed elevated serum FSH levels in women of advanced reproductive age [76][77][78][79][80][81].…”
Section: Menopausementioning
confidence: 99%
See 1 more Smart Citation